1.
3x - 4y = 7
3x = 7 + 4y
x = (7/3) + (4/3)y
2.
a(y + 1) = b
y + 1 = b/a
y = (b/a) - 1
3.
ex - 2y = 3z
ex = 3z + 2y
x = (3/e)z + (2/e)y
4.
(3/5)y + a = b
(3/5)y = b - a
y = (5/3)b - (5/3)a
5.
mx + b = y
mx = y - b
m = (y/x) - (b/x)
2007-09-04 06:46:01
·
answer #1
·
answered by Anonymous
·
0⤊
2⤋
I won't do your homework for you, but I'll help you with the first one...
All you have to do is get the letter you are trying to solve for by itself on one side of the equal sign. So in the first question, you have:
3x - 4y = 7
so to get x by itself, we have to get rid of that 4y on the left of the equal sign. So if we ADD 4y to BOTH sides of the equal sign, you get:
3x - 4y + 4y = 7 + 4y
Now, if you just look at the last two values on the left of the equal sign, you see (-4y + 4y), which equals 0, so it can just go away (that's the reason we did it in the first place!) so now you have
3x = 7 + 4y
so, the only letter on the left of the equal sign is x, so that's good, but we still have that 3 there, so we can get rid of it by dividing both sides by 3. (Remember, you always have to do the same thing to both sides of the equal sign, or they won't be equal anymore and the answer will be wrong)
So, dividing both sides by 3 gives you:
x = (7 +4y) / 3
Ok...I'm feeling generous, so let's look at the second one...I don't like those parenthesis, so let's get rid of those first:
a(y + 1) = b --> ay + a = b (The distributive property, remember?)
now, get rid of the " + a" on the left:
ay = b - a
now divide both sides by a:
y = (b-a)/a
If you do the distributive property again, you can write that as
y = b/a -1
Can you do the rest?
2007-09-04 14:00:45
·
answer #2
·
answered by lllomaxxx 2
·
0⤊
1⤋
1. 3x - 4y = 7, for x
3x = 4y+7 --> x = (4y+7)/3
2. a(y + 1) = b, for y
ay+a = b --> ay= (b-a) --> y = (b-a)/a
3. ex - 2y = 3z, for x
ex = 3z+2y --> x = (3z+2y)/e
4. 3/5y + a = b, for y
3y/5 = b-a --> y = 5(b-a)/3
5. y = mx + b, for m
mx= y-b --> m= (y-b)/x
2007-09-04 13:54:04
·
answer #3
·
answered by ironduke8159 7
·
0⤊
1⤋
you should get off answers and study some algebra
1. (4y-7)/3
2. b/a -1
3. (3z+2y)/e
4. [5*(b-a)]/3
5. (y-b)/x
2007-09-04 13:49:42
·
answer #4
·
answered by Ilya S 3
·
0⤊
1⤋
3x-4y=7
3x=4y+7
a(y+1)=b
ay+a=b
y= b/2a
ex-2y=3z
x-2y=3z/e
x= 2y + 3z over e
3/5y + a=b
3/5 y= b-a
y= b-a over .6 (3/5)
y=mx+b
mx= y-b
m= y-b over x
(y-b) over x = m
2007-09-04 13:51:45
·
answer #5
·
answered by lennadwyer2 2
·
0⤊
2⤋
Since you can solve the first one, it's kinda weird that you can't solve the rest.............
I'll only do 1 and 5 for you.
x = (7 + 4y)/3
m = (y - b)/x
Go practice and do the rest
2007-09-04 13:49:33
·
answer #6
·
answered by Bananaman 5
·
0⤊
1⤋
1. x = (7+4y)/3
2. y = (b-a)/a
3. x = (3z+2y)/e
4. y = 5(b-a)/3
5. m = (y/x) -b
2007-09-04 13:51:58
·
answer #7
·
answered by Anonymous
·
0⤊
2⤋
you will never undrestand questions like this if you ask everyone else to do it or you.COMMON SENCE!PEACE!
2007-09-04 13:48:10
·
answer #8
·
answered by charitymcgee 1
·
0⤊
2⤋